Assessment of the effects of Eleutherococcus Senticosus on endurance performance - Goulet, E. D. B.; Dionne, I. J. (International Journal of Sport Nutrition and Exercise Metabolism, 2005)
The use of nutritional ergogenic aids containing Eleutherococcus senticosus (ES), a plant which is also known as ciwujia or Siberian ginseng, is relatively common among endurance athletes. Eleutherococcus senticosus has been suggested to improve cardiorespiratory fitness (CF) and fat metabolism (FAM) and, therefore, endurance performance (EP). This article reviews the studies that evaluated the effects of ES during endurance exercise, three of which suggest that ES substantially improves CF, FAM, and EP. However, each of these reports contains severe methodological flaws, which seriously threaten their internal validity, thereby rendering hazardous the generalization of the results. On the other hand, 5 studies that used rigorous research protocols show no benefit of ES on CF, FAM, and EP. It is therefore concluded that ES supplementation (up to 1000 to 1200 mg/d for 1 to 6 wk) offers no advantage during exercise ranging in duration from 6 to 120 min.